2013
DOI: 10.1590/s1413-35552012005000118
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quality-of-life instruments for assessing the participation after stroke based on the International Classification of Functioning, Disability and Health (ICF)

Abstract: | Background: According to the International Classification of Functioning, Disability and Health (ICF), the participation component is considered to be the most complex component characterized in existing instruments that assess quality of life related to health (HRQoL). Questionnaires such as the Nottingham Health Profile (NHP) and the Stroke-Specific Quality of Life (SS-QOL) are currently used to evaluate the participation of individuals in life activities after stroke. However, because participation and HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
0
16
0
4
Order By: Relevance
“…Identification of the items of the SS-QOL that address the ICF participation component was based on a study by Silva et al 11 ) , who found that 26 of the 49 SS-QOL items evaluated participation, spanning eight subscales (family roles, language, mobility, self-care, social roles, thinking, upper extremity function, and work/productivity). Five response options are offered for each item, with item scores ranging from 1 to 5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification of the items of the SS-QOL that address the ICF participation component was based on a study by Silva et al 11 ) , who found that 26 of the 49 SS-QOL items evaluated participation, spanning eight subscales (family roles, language, mobility, self-care, social roles, thinking, upper extremity function, and work/productivity). Five response options are offered for each item, with item scores ranging from 1 to 5.…”
Section: Methodsmentioning
confidence: 99%
“…Five response options are offered for each item, with item scores ranging from 1 to 5. Thus, the minimum overall score for the questionnaire is 26 (lowest social participation), and the maximum score is 130 (highest social participation) 11 ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos apresentam ferramentas similares de codificação através da CIF com escalas e questionários já validados, como é o caso do índice de Barthel 23 a MIF 24 e do questionário de qualidade de vida 25 , entretanto ainda não foram propostas essas associações para caracterização da funcionalidade de paciente 26 .…”
Section: Discussionunclassified
“…In recent years, knowledge of the recovery phase of stroke has expanded rapidly, and the number of stroke survivors has grown due to advances in acute-phase treatments 4 ) . One report projects that survival after the onset of stroke will increase gradually throughout the world, and almost 90% of those survivors will have a disability 5 ) .The Republic of Korea is no exception to these trends. A number of studies have focused on the causes of stroke, first aid, and intervention methods, but despite these projections, epidemiologic surveys on stroke have been limited 6 , 7 ) .…”
Section: Introductionmentioning
confidence: 99%